Suppressing Interfacial Shunt Loss via Functional Polymer for Performance Improvement of Lead‐Free Cs2AgBiBr6 Double Perovskite Solar Cells. Issue 4 (3rd December 2021) - Li, Jiabao; Yan, Furi; Yang, Peizhi; Duan, Yanyan; Duan, Jialong; Tang, Qunwei
Abstract : All‐inorganic lead‐free Cs2 AgBiBr6 double perovskite solar cells (PSCs) have attracted growing attention owing to their eco‐friendly features and robust intrinsic stability. However, arising from the rapid crystal growth, the poor film quality always leads to substantial non‐radiative recombination and inferior performance improvement. Herein, high‐efficiency and stable Cs2 AgBiBr6 PSCs are obtained by introducing a functional polymethyl methacrylate (PMMA) layer at the perovskite surface to avoid direct contact between carbon and the underlying charge transfer layer, as well as to passivate the defects. When assembling into solar cells, the non‐radiative charge recombination is suppressed and the interfacial charge extraction is accelerated. As a result, the carbon‐electrode‐based Cs2 AgBiBr6 PSC yields an enhanced efficiency of 2.25% with a high open‐circuit voltage of 1.18 V. Moreover, the unencapsulated device exhibits superior long‐term stability owing to the protection of the PMMA layer from corrosion by the extraneous water and oxygen, retaining nearly 100% of the initial efficiency after storage in 25 °C, with 5% relative humidity (RH) for 80 days and high temperature of 85 °C, and 0% RH for 60 days, respectively. A simple method of polymer passivation for enhancing the performance and stability of Pb‐free Cs2 AgBiBr6 PSCs is provided. Abstract : By inserting a functional polymer polymethyl methacrylate thin layer at the perovskite interface, the hole transfer layer (HTL)/Pb‐free carbon‐electrode‐based Cs2 AgBiBr6 perovskite solar cell achieves an enhanced power conversion efficiency of 2.25% with a high open‐circuit voltage of 1.18 V owing to the reduced defects and suppressed short‐circuit‐induced shunt loss.